A study on a relationship of ambient condition and employee health in SOCSO Office at Kuala Kangsar, Perak / Nor Akidah Masa, Nurul Hanani Abdul Halim and Siti Munirah Mohamad Amir - Masa, Nor Akidah; Abdul Halim, Nurul Hanani; Mohamad Amir, Siti Munirah (2011)
An open-plan office is an office setting where the employees have a workstation in one room. Whether one would find a single room office or an open-plan office when walking into an office building was a toss-up in the industrial world during the eighties. Even companies in the same business had different preferences when it came to the question of single rooms or open-plan offices (Stone and Luchetti, 1985). Nowadays, the majority of the offices in certain country such as Sweden are designed as single room offices but trend is towards a majority of open-plan offices within a near future (Aronsson, 2005). The open-place office concept conversely, is based on the relationship of the employee and his or her job duty, which is more consistent with office ergonomics to ensure employee perform well (Quible Zane, 2005). Its popularity is increasing because it provided a cost effective method for making layout changes. The open office concept tends to locate the workstations of many employees in close proximity to one another.